Investigating Secondary Regular Classroom Teachers’ Intervention to Accommodate Students with Dyslexia in a Private School in Dubai, UAE: Exploratory Case Study - ELFAR, GHADA FARAG (2022)
This exploratory case study aims to determine which extinct secondary school teachers in a private school in Dubai, UAE use successful intervention to accommodate students with dyslexia in the regular classroom, as well as the obstacles they may face. The study also sheds light on the hurdles secondary school students with dyslexia may encounter and how to overcome these obstacles. Interviews and surveys were used as part of a mixed-methods strategy to obtain qualitative and quantitative data. The findings demonstrate that secondary regular classroom instructors had a limited awareness of dyslexia as a reading disability and were confused by dyslexia features. Some parents' responses to interview questions suggested dissatisfaction with the intervention's outcomes on their children. Concerns raised by several parents demonstrated a link between instructors' lack of comprehension of dyslexia's characteristics as well as inability to identify their children's unique skills, and the ineffectiveness of some classroom teachers' interventions. Majority of secondary instructors highlighted that class size, the length of the curriculum, lack of teaching tools, the pace of lessons, lack of human resources, parental denial and lack of parental cooperation are hurdles to addressing the requirements of students with dyslexia in the classroom. The findings also showed recommendations for better practice, such as dyslexia training for regular classroom teachers, adopting teaching tactics that accommodate the special requirements of students with dyslexia, recognizing students' learning styles, and communicating with parents and educators. Some participants underlined the need of boosting secondary students with dyslexia self-esteem, which might be a topic for future research. Additionally, the study's limitations and the need for future research were addressed.